Accuracy of standardized 12‐core template biopsies versus non‐standardized biopsies for detection of Epstein Grade 5 prostate cancer regarding the histology of the prostatectomy specimen. Issue 5 (25th January 2018) - Würnschimmel, Christoph; Grande, Pietro; Moschini, Marco; Ferrari, Matteo; Mordasini, Livio; Mattei, Agostino
Abstract : Objective: To evaluate the effectiveness of EAU Guideline compliant transrectal ultrasound‐guided 12‐core prostate biopsies for detection of highly aggressive Epstein Grade 5 (Gleason Score 9‐10) prostate cancer. Methods: Two hundred ninety‐nine patients, treated by radical prostatectomy for prostate cancer, have been prospectively recorded in a database and were evaluated for this study. Pre‐operatively, all patients received transrectal ultrasound‐guided biopsies according to inhomogeneous templates chosen by the referring urologist. We evaluated the outcomes according to a stratified group‐analysis: Group 1 received less than 12 biopsies, Group 2 received more than 12 biopsies, and Group 3 received exactly 12 biopsies, according to the EAU Guidelines template. After surgical removal of the prostate, 12 EAU Guideline‐templated biopsies were performed in all prostatectomy specimens, directly after the surgery. Pre‐operative and post‐operative Epstein Grade 5 biopsy detection rates were thereafter correlated with these prostatectomy specimens. Results: In prostatectomy specimens, the histology of 12 patients (4.0%) were Epstein Grade 1, 31 patients (10.5%) were Epstein Grade 2, 190 patients (63.5%) were Epstein Grade 3, 27 patients (9%) were Epstein Grade 4, and 39 patients (13%) were Epstein Grade 5. The detection rate of Epstein Grade 5 compared to the radical prostatectomy specimen was: Group 1: 23.0% pre‐operatively and 61.5% post‐operatively, Group 2: 33.3% pre‐operatively and 58.3% post‐operatively; and Group 3: 57.1% pre‐operatively and 64.2% post‐operatively. Conclusion: Detection rates of highly aggressive Epstein Grade 5 prostate cancer vary considerably according to the biopsy technique. EAU Guideline compliant 12‐core template biopsies increase the detection rates of Epstein Grade 5 prostate cancer.